Effect of colistin exposure and growth phase on the surface properties of live Acinetobacter baumannii cells examined by atomic force microscopy - Soon, Rachel L. (2011)
The diminishing antimicrobial development pipeline has forced the revival of colistin as a last line of defence against infections caused by multidrug-resistant Gram-negative ‘superbugs’ such as Acinetobacter baumannii. The complete loss of lipopolysaccharide (LPS) mediates colistin resistance in some A. baumannii strains. Atomic force microscopy was used to examine the surface properties of colistin-susceptible and -resistant A. baumannii strains at mid-logarithmic and stationary growth phases in liquid and in response to colistin treatment. The contribution of LPS to surface properties was investigated using A. baumannii strains constructed with and without the lpxA gene. Bacterial spring constant measurements revealed that colistin-susceptible cells were significantly stiffer than colistin-resistant cells at both growth phases (P < 0.01), whilst colistin treatment at high concentrations (32 mg/L) resulted in more rigid surfaces for both phenotypes. Multiple, large adhesive peaks frequently noted in force curves captured on colistin-susceptible cells were not evident for colistin-resistant cells. Adhesion events were markedly reduced following colistin exposure. The cell membranes of strains of both phenotypes remained intact following colistin treatment, although fine topographical details were illustrated. These studies, conducted for the first time on live A. baumannii cells in liquid, have contributed to our understanding of the action of colistin in this problematic pathogen.